Методична освіта вчителів історії (на прикладі піготовки до викладання iсторії України) - Прокопчук, Вікторія Євгенівна; Prokopchuk, Viktoriia Ye. (Інститут системних досліджень освіти, 1995)
У статті представлена структура змісту методичної освіти, форми навчально-виховного процесу. Виходячи зі змісту методичної освіти, тезово перераховані знання студентів з методики викладання історії. Вивчення методики пропонується поділити на 5 змістових блоки. Розглядаються форми та методи методичної освіти.

The article presents the structure of the content of methodological education, the form of the educational process. Based on the content of methodological education, the aforementioned knowledge of students on the methodology of teaching history. The study methodology is proposed to be divided into 5 content blocks. Form and methods of methodological education are considered.
Methodological application of history teachers (on an example of preparation for the teaching of the history of Ukraine)
Keywords: освіта; методична освіта; навчально-виховний процес; форми методичної освіти; зміст методичної освіти; education; methodological education; educational process; forms of methodological education; content of methodological education